Study of cryptographic attacks on the digital signature scheme in quotient ring of truncated polynomials - Кузнецов, Олександр Олександрович; Горбенко, Юрій Іванович; Шевцов, Олексій Володимирович; Кузнецова, Тетяна Юріївна (Ukrainian Information Security Research Journal, 2016)
One of the main techniques obtaining authentication is using digital signatures. Research of posquantum digital signatures now acquired urgency because of the potential appearance of quantum computer. Lattice based cryptosystems have several advantages, among which are resistance to quantum cryptanalysis. Therefore, the question of security of lattice based signatures requires detailed analysis. A model of forgery attack using annihilating polynomials against NTRUSign with strengthened parameters and perturbations is proposed. Also we analyse the effectiveness of NTRUSign counterfeiting in practice. The experimental estimates of NTRUSign enhanced parameter settings to this type of threat are considered. The practical value of the obtained results is the experimental evidence that the effectiveness of attack is not significantly reduced by increasing the signature parameter.